Three-dimensional analysis of facial changes in skeletal Class III patients following mandibular setback surgery - Nishino, Kazuomi; Kohara, Akihiro; Yakita, Yuri; Ochi, Kanako; Hayashi, Takafumi; Takagi, Ritsuo; Kobayashi, Tadaharu; Terada, Kazuto; Saito, Isao (Journal of oral and maxillofacial surgery, medicine, and pathology, 2016)
To identify the degree of correlation of various parameters using multiple linear regression analysis with soft tissue changes as the response variable. The subjects comprised 10 skeletal Class III patients who had undergone bilateral sagittal split osteotomy (BSSO). The candidates for the explanatory variables included 10 parameters, such as overjet, overbite, sella–nasion–A point angle (SNA), upper incisor inclination (U1-SN), incisor mandibular plane angle (IMPA), gonial angle, nasolabial angle, menton deviation, soft tissue thickness, and hard tissue changes. These parameters were measured using cephalograms, dental cast models, and a three-dimensional integration model. Finally, 5 parameters were chosen as explanatory variables. A standard regression coefficient (β value) and an adjusted R-square (R*2 value) were used to assess correlations between soft tissue changes and to evaluate the regression equation. In the zygomatic arch and maxillary regions, β values for overjet and SNA were particularly positive and high, whereas those for hard tissue changes were negative and low. In the mandibular central regions, β values for hard tissue changes were positive and high. In the other mandibular regions, β values for menton deviation were higher than those for hard tissue changes. The R*2 values in all regions were greater than 0.5. Overjet and SNA were more strongly associated with soft tissue changes in the zygomatic arch maxillary regions than hard tissue changes. The extent of mandibular retraction and menton deviation was highly correlated with the mandibular central regions and the other mandibular regions, respectively.